Role of cytokines in pathogenesis, diagnosis and efficiency evaluation of immunotherapy in various variants of sclerotic lichen in women - E. V. Kolesnikova; A. V. Zharov; G. A. Penzhoyan (Медицинская иммунология)
Our aim was to evaluate diagnostic and pathogenetic significance of plasma cytokines (IL-20, IL-23, IL-10, TNFα, IFNγ) in the patients with various clinical and histological variants of sclerotic lichen and to assess opportunity for their use as effectiveness criteria of immunotherapy for this disease using a drug based on eukaryotic deoxyribonucleic acid (Derinat). The prospective cohort study included assessment of the clinical manifestations (itching and dyspareunia) and measurement of blood cytokine contents (IL-20, IL-23, IL-10, TNFα, IFNγ) in women (n = 114) with various clinical variants of sclerotic lichen (atrophic, sclerotic and sclerotic-atrophic) before and after immunotherapy with a nucleic acid-based drug (Derinat). Derinat was chosen due to the fact of being an agonist of Toll-like receptors, and a number of immunoregulatory effects, including the ability to modulate cytokine production and to exert a positive influence upon regeneration processes. In addition, based on visual inspection, vulvoscopy and morphohistochemical examination results (evaluation criteria: skin thickness, number of collagen fibers, severity of fibrosis and sclerosis, etc.), the corresponding subgroups were classified within the II group, i.e., 2.1 (minimal sclerotic signs, n = 14), and 2.2 (pronounced sclerotic signs, n = 20). The control group consisted of conditionally healthy women, without history or presence of vulvar pathology (n = 30), with an age ranging from 20 to 50 years. Along with cytokine assessment by enzyme immunoassay, the study used the data of clinical examination (anamnesis collection, examination, palpation, vulvoscopy), as well as complex morphohistochemical evaluation of vulvar tissues. In atrophic variant, we have observed an increase in plasma IL-23 content, along with decreased TNFα; in lichen sclerosis, a maximal increase in IL-20, IL-23, and IFNγ was revealed; in sclerotic form of sclerotic lichen variant with severe sclerotic features, maximally enhanced IL-20, IL-23, TNFα, IFNγ, along with minimal levels of IL-10 was registered, as compared with other groups. Immunotherapy using Derinate resulted into significant reduction in the clinical manifestations in sclerotic lichen, i.e., itching of the vulva and dyspareunia, as well as normalization of cytokine indexes. Our studies have demonstrated an opportunity of using plasma concentrations of IL-20, IL-23, IL-10, TNFα, IFNγ as biomarkers of sclerotic lichen variants, and as laboratory criteria for efficiency of immunotherapy.